Globalisation and Food Sovereignty: Impact of Foreign Direct Investments and Government Expenditure in Ghana in 2001–2010 - Martin Páral; Petr Blížkovský (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2019)
The article looks at the globalisation effects on food availability in Ghana. The aim of the article is to analyse which of the selected macroeconomic indicators have a statistically significant impact on the increase of food availability in the country. Impacts of foreign direct investments on agriculture and government expenditures in agriculture have been tested. Correlation analyses and multiple regression analyses have been used to analyse the test results. Findings suggest that change in both foreign direct investments in agriculture and government expenditures in agriculture cause significant change in food availability in Ghana. At the same time, the impact of government expenditures on the amount of available food is in the case of Ghana more than two‑times higher than the impact of agricultural foreign direct investments, while the increase in government expenditures in agriculture does not cause a decrease in foreign direct investments in agriculture.